2019
DOI: 10.1016/j.proci.2018.06.122
|View full text |Cite
|
Sign up to set email alerts
|

A mixture-fraction-based hybrid binomial Langevin-multiple mapping conditioning model

Abstract: Generalized Multiple Mapping Conditioning (MMC) allows for the use of any physical quantity to represent the required reference variable provided that it delivers the desired behavior. The binomial Langevin model (BLM) has been shown to predict higher statistical moments with good accuracy. However, joint-scalar modeling for many scalars becomes problematic because scalar bounds must be specified as conditional on other scalars to preserve elemental balances. The resulting volumes in state space become excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the current case, comparisons with measurements of temperature, the OH radical, molecular oxygen, molecular hydrogen, carbon monoxide and the PDF of temperature are consistent with the above explanation of the impact of molecular diffusion in physical space. A comparison with results obtained by Wandel and Lindstedt [43] suggests that models for molecular mixing that enforce locality in composition space [20,21,23,55] can mitigate against short comings of simpler models in the treatment of molecular diffusion, particularly when applied in the context of moment based closures. The current work has shown that the developed approach is viable for well-resolved boundary layer flows and it can be expected that the same applies to the computation of premixed turbulent flame structures at high Da numbers [30,52].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the current case, comparisons with measurements of temperature, the OH radical, molecular oxygen, molecular hydrogen, carbon monoxide and the PDF of temperature are consistent with the above explanation of the impact of molecular diffusion in physical space. A comparison with results obtained by Wandel and Lindstedt [43] suggests that models for molecular mixing that enforce locality in composition space [20,21,23,55] can mitigate against short comings of simpler models in the treatment of molecular diffusion, particularly when applied in the context of moment based closures. The current work has shown that the developed approach is viable for well-resolved boundary layer flows and it can be expected that the same applies to the computation of premixed turbulent flame structures at high Da numbers [30,52].…”
Section: Discussionmentioning
confidence: 81%
“…The standard mixing time scale closure given in Eq. ( 15) with C ϕ = 2.3 [48] is applied here for consistency with previous work [42,43].…”
Section: A Jpdf Methods With Molecular Transport In Physical Spacementioning
confidence: 97%
See 1 more Smart Citation
“…Another advantage is that a number of constraints are respected, such as the boundedness, linearity, independence and the Gaussian limiting behaviour. In [89], a further study is reported on coupling the BLM with the multiple mapping conditioning (MMC) of [88]. The authors advocate the use of mixture fraction statistics in MMC to outperform other approaches, including those based on LES.…”
Section: More Models Of Scalar Mixingmentioning
confidence: 99%
“…Flames HM2 and HM3 have proved more challenging due to the enhanced probability of local extinction and the co-existence of diffusion flames and premixed gas pockets. Multiple Mapping Conditioning (MMC) [30] has also been used for diffusion flames [31] with local extinction [32] and has recently extended to premixed combustion [33]. Transported JPDF method [24][25][26]28] can in principle predict flames with high levels of local extinction as well as re-ignition.…”
Section: Introductionmentioning
confidence: 99%